Displacement patterns of stranded I-125 seeds after permanent brachytherapy of the prostate: Dosimetry in the operating room put into perspective. Issue 1 (July 2017) - Steggerda, Marcel J.; van den Boom, Ferrie; Witteveen, Thelma; Moonen, Luc M.F.
Abstract: Background and purpose: The reliability of post-implant dosimetry in the OR depends on the geometrical variability of implant and anatomy after the procedure. The purpose was to gain detailed information on seed displacement patterns in different sectors of the prostate. Materials and methods: Of 33 patients with stranded seed implants the seed geometry and the dose distribution were compared between the situation in the OR just after the procedure, based on ultrasound images, and the situation after 1 month, based on registered CT and MR images. Results: There was a substantial displacement of ventral seeds of 3.8 ± 2.5 mm in caudal direction ( p < 0.001). Of these ventral seeds cranially located seeds moved more than caudally located seeds, 4.5 ± 2.7 mm and 2.9 ± 2.6 mm, respectively ( p < 0.001). The D 90 in the dorsal-caudal and ventral-caudal sectors increased with respectively 44 ± 20 Gy and 29 ± 28 Gy ( p < 0.001) and decreased with 17 ± 31 Gy in the ventral-cranial sector ( p = 0.008). Conclusions: There were substantial changes in dose distribution 1 month after the procedure, mainly due to implant and prostate shrinkage and displacement of ventral seed strands in caudal direction. When performing dynamic dosimetry or dosimetry at the end of the procedure the effect of these phenomena has to be taken into account when using stranded seeds.